Karakterisasi fisik, kimia dan komponen bioaktif kerang gerigi dari perairan Pulau Kulambing Kabupaten Pangkajene dan Kepulauan - Inthe, Mita Gebriella; Rusli, Arham; Mursida, Mursida; Azima, Afifah (Politeknik Pertanian Negeri Pangkajene Kepulauan, 2025)
Kulambing Island, located in Pangkajene Islands Regency, South Sulawesi, is rich in marine biodiversity, including a type of mollusc known as shellfish. One of the shellfish that local people widely consume is the serrated clam. This study aims to determine the physical, chemical, and bioactive component characteristics originating from Kulambing Island. This research was conducted from October to December 2024. The physical parameters analyzed included morphometric and chemical parameters, including water content, protein, fat, ash, carbohydrate, and bioactive component tests. The study’s results showed that the serrated clam had a shell length of 6.62 cm, a width of 5.21 cm, and a thickness of 3.51 cm, with a meat yield of 14.06% and a shell of 85.93%. The chemical composition of the clam contains 76.2% water, 17.88% protein, 2.88% fat, 0.97% ash, and 2.07% carbohydrates. The bioactive content contained in the clams includes alkaloids, phenols, and saponins.